Effect of Freshwater Algal Extracts as Foliar Applications on Biometric Parameters of Safflower (Carthamus tinctorious L.) (International Journal of Food and Nutritional Sciences, 2022)
The present investigation demonstrates that freshwater algal extracts, particularly those collected from the Pravara Left Canal, exert a significant positive impact on the biometric parameters of Safflower (Carthamus tinctorius L.) when applied as foliar sprays. Among all treatments, the 20% algal extract combined with cow urine (T6) showed the maximum improvement in plant growth attributes, including number of leaves, leaf area, number of branches, and plant height, compared to both the control and other treatments.The enhanced growth performance is attributed to the synergistic effect of bioactive compounds present in freshwater algae such as phytohormones, amino acids, vitamins and micronutrients along with the nutrient-rich composition of cow urine. Statistical analysis using two-way ANOVA confirmed that the observed differences were highly significant (p < 0.05), especially in the T6 treatment, indicating the strong potential of cow urine-enriched algal extracts as natural bio-stimulants. Furthermore, algal extracts from the Pravara Left Canal proved more effective than those from the Pravara River, possibly due to variations in species composition, nutrient content and ecological conditions. These findings are consistent with earlier studies reporting the beneficial role of algal extracts in enhancing the growth of various crops, including fenugreek, spinach, chilli, tomato and alfalfa.The study concludes that locally available freshwater algae can serve as a cost- effective, eco-friendly alternative to chemical fertilizers. Integrating these natural bio- resources into sustainable agricultural practices could improve crop productivity, reduce chemical dependency and promote environmentally friendly farming systems in the Pravara River basin and other similar agro-ecological regions.